A survey on the computerized based accounting system use among manufacturing companies in Kuching, Sarawak / Corina Joseph … [et al.] - Joseph, Corina; Janggu, Tamoi (2003)
This study reports on the survey of computerized based accounting system (CBAS) use among the manufacturing companies in Kuching Sarawak. As there is limited published research carried out on this area, this report aims to identify the extent of CBAS adopted in the Sarawak manufacturing companies. This study is conducted through the questionnaire survey method. Besides exploring the types of accounting software adopted, this study also attempts to investigate the problems and impact in using the CBAS on the employees' work productivity. The results of this study have revealed that the CBAS is moderately used in the companies. The statistical analysis demonstrates that the respondents disagree to all the problems listed in the questionnaire distributed to them and gave positive responses to all the impacts listed in the questionnaire in using the CBAS and on the work productivity. The study concludes that the average adoption rate among the respondents is attributed to small size of the companies, lack of exposure and awareness, attitude problem, business needs and requirement and others. Some recommendations have been made to improve the existing scenario.